2018
DOI: 10.1097/md.0000000000012212
|View full text |Cite
|
Sign up to set email alerts
|

Hospital readmission with Clostridium difficile infection as a secondary diagnosis is associated with worsened outcomes and greater revenue loss relative to principal diagnosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“… 17 Among patients readmitted with rCDI in the State Inpatient Databases, there is a significant gap in reimbursement of almost US $8000 to US $18,000 for patients who present with rCDI and septicemia on admission. 18 There are several theories regarding the pathophysiological basis for BSI in patients with CDI and rCDI. Most focus on disruption of the gut microbiota and/or a cellular inflammatory response, resulting from an impaired gut barrier function and immune response to CDI toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Among patients readmitted with rCDI in the State Inpatient Databases, there is a significant gap in reimbursement of almost US $8000 to US $18,000 for patients who present with rCDI and septicemia on admission. 18 There are several theories regarding the pathophysiological basis for BSI in patients with CDI and rCDI. Most focus on disruption of the gut microbiota and/or a cellular inflammatory response, resulting from an impaired gut barrier function and immune response to CDI toxins.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In patients readmitted for rCDI after a major operating room procedure, there is average reimbursement gap of US $20,000. 18 …”
Section: Discussionmentioning
confidence: 99%
“…A survey of the State Inpatient Databases reported a LOS of 7.3 days for a primary rCDI diagnosis in U.S. adults. 30 Excess LOS attributable to CDI is approximately 3 days. 31 A previous analysis of Medicare claims data for patients with community-acquired CDI showed a median hospital LOS of 5 days (interquartile range, 3-8 days).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by other studies of readmissions in CDI that report rates of 25-30% readmission and prolonged duration of hospitalization. In a retrospective cohort study of 385,682 initial CDI hospitalizations identified between years 2009 and 2013 in the 4 states included in the State Inpatient Database (AHRQ), 25.7% of patients required readmission; among these, 36.8% had recurrent CDI as the principal diagnosis at the time of readmission [33]. A study of data from the Healthcare Cost and Utilization Project (HCUP) saw that patients with a primary or secondary diagnosis of CDI had a 30-day readmission rate of 29.1% [34].…”
Section: Discussionmentioning
confidence: 99%